Level of Pest Infestation on Cocoa (Theobroma cacao L.) Variety BL-50 in Tanah Datar Regency, West Sumatera Province, Indonesia - Zahlul Ikhsan; Muhammad Al-Ikhlas; Yaherwandi; Hasmiandy Hamid; Aulia Oktavia; Dandy Ahamefula Osibe (Andalasian International Journal of Entomology, 2024)
West Sumatra Province is one of the cocoa production centers in Indonesia. Cocoa farmers in the Lima Puluh Kota District in West Sumatera Province had successfully developed a superior clone of cocoa plants resulting from participatory selection, which was later coded BL-50. The main pests that attack cocoa plants are the urgent problem in cocoa cultivation, resulting in decreased productivity. This study aims to determine the level of significant pest attacks on cocoa varieties BL-50 in Tanah Datar Regency. This research is in the form of a survey with a purposive sampling method. Sampling is carried out systematically diagonally in the field. The highest attack rate of Cocoa Fruit Borer in Tanah Datar Regency is in Rambatan District, with the percentage of affected plants, the percentage of infested fruits, and the highest attack intensity, respectively 51,.25%; 31.58% and 21.10%, the lowest were in Lintau Buo Utara District with 30.93%; 20.70% and 13.96%. The highest attack rate of cocoa fruit-sucking ladybugs in the BL-50 variety is in Rambatan District, 66.09%, 45.07%, and 30.45%. At the same time, the lowest is in the Lintau Buo Utara District, with a percentage value of 41.56%, 27.66%, and 18.30%. Excellent and regular land sanitation activities have played a role in minimizing the level of pest attacks in Lintau Buo Utara.